The KCa2 Channel Inhibitor AP30663 Selectively Increases Atrial Refractoriness, Converts Vernakalant-Resistant Atrial Fibrillation and Prevents Its Reinduction in Conscious Pigs - Diness, Jonas Goldin; Kirchhoff, Jeppe Egedal; Speerschneider, Tobias; Abildgaard, Lea; Edvardsson, Nils; Sørensen, Ulrik S.; Grunnet, Morten; Bentzen, Bo Hjorth (Frontiers in Pharmacology, 2020)
Aims: To describe the effects of the KCa2 channel inhibitor AP30663 in pigs regarding tolerability, cardiac electrophysiology, pharmacokinetics, atrial functional selectivity, effectiveness in cardioversion of tachy-pacing induced vernakalant-resistant AF, and prevention of reinduction of AF. Methods and results: Six healthy pigs with implanted pacemakers and equipped with a Holter monitor were used to compare the effects of increasing doses (0, 5, 10, 15, 20, and 25 mg/kg) AP30663 on the right atrial effective refractory period (AERP) and on various ECG parameters, including the QT interval. Ten pigs with implanted neurostimulators were long-term tachypaced until sustained vernakalant-resistant AF was present. 20 mg/kg AP30663 was tested, to discover if it could successfully convert vernakalant-resistant AF to SR and protect against reinduction of AF. Seven anaesthetized pigs were used for pharmacokinetic experiments. Two pigs received an infusion of 20 mg/kg AP30663 over 60 minutes while five pigs received 5 mg/kg AP30663 over 30 minutes. Blood samples were collected before, during and after infusion on AP30663. AP30663 was well-tolerated and prominently increased the AERP in pigs with little effect on ventricular repolarization. Furthermore, it converted A-TP induced AF that had become unresponsive vernakalant, and it prevented reinduction of AF in pigs. Both a >30 ms increase of the AERP and conversion of AF occurred, in different pigs, at a free plasma concentration level of around 1.0-1.4 µM of AP30663, which was achieved at a dose level of 5mg/kg. Conclusion: AP30663 has shown properties in animals that would be of clinical interest in man